2018
DOI: 10.1007/s00784-018-2360-y
|View full text |Cite
|
Sign up to set email alerts
|

Health and quality of life differ between community living older people with and without remaining teeth who recently received formal home care: a cross sectional study

Abstract: ObjectiveTo assess oral health, health, and quality of life (QoL) of care-dependent community-living older people with and without remaining teeth who recently received formal home care.Materials and methodsFor this cross-sectional observational study, community-living older people (≥ 65 years), who recently (< 6 months) received formal home care, were interviewed with validated questionnaires and underwent an oral examination. Oral health, general health, medicines usage, frailty (Groningen Frailty Indicator)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 31 publications
2
55
1
Order By: Relevance
“…All reported associations regarding edentulism, number of teeth, number of missing teeth, and number of occluding pairs are shown in Table 2. Five studies reported significantly lower OHQoL in edentulous participants than in dentate participants (Hoeksema et al, 2017;Hoeksema et al, 2018;Motallebnejad, Mehdizadeh, Najafi, & Sayyadi, 2015;Stromberg, Holmen, Hagman-Gustafsson, Gabre, & Wardh, 2013;Zuluaga, Montoya, Contreras, & Herrera, 2012), two studies demonstrated a positive association between edentate patients in comparison to dentate patients and OHQoL (Lee, Yang, Ho, & Lee, 2012;Souza, Costa Oliveira, & Martins, 2017), and seven studies reported no significant association between edentulism and OHQoL (Alshammari, Baseer, Ingle, Assery, &Al Khadhari, 2018;Cornejo, Perez, de Lima, Casals-Peidro, & Borrell, 2013;Dahl, Wang, Holst, & Ohrn, 2011;Kohli, Sehgal, Nelson, & Schwarz, 2017;Rebelo, Cardoso, Robinson, & Vettore, 2016;Sheiham et al, 2001;Yu, Lee, Hong, Lau, & Leung, 2008). All studies regarding edentulism were crosssectional studies.…”
Section: Natural Dentitionmentioning
confidence: 99%
See 2 more Smart Citations
“…All reported associations regarding edentulism, number of teeth, number of missing teeth, and number of occluding pairs are shown in Table 2. Five studies reported significantly lower OHQoL in edentulous participants than in dentate participants (Hoeksema et al, 2017;Hoeksema et al, 2018;Motallebnejad, Mehdizadeh, Najafi, & Sayyadi, 2015;Stromberg, Holmen, Hagman-Gustafsson, Gabre, & Wardh, 2013;Zuluaga, Montoya, Contreras, & Herrera, 2012), two studies demonstrated a positive association between edentate patients in comparison to dentate patients and OHQoL (Lee, Yang, Ho, & Lee, 2012;Souza, Costa Oliveira, & Martins, 2017), and seven studies reported no significant association between edentulism and OHQoL (Alshammari, Baseer, Ingle, Assery, &Al Khadhari, 2018;Cornejo, Perez, de Lima, Casals-Peidro, & Borrell, 2013;Dahl, Wang, Holst, & Ohrn, 2011;Kohli, Sehgal, Nelson, & Schwarz, 2017;Rebelo, Cardoso, Robinson, & Vettore, 2016;Sheiham et al, 2001;Yu, Lee, Hong, Lau, & Leung, 2008). All studies regarding edentulism were crosssectional studies.…”
Section: Natural Dentitionmentioning
confidence: 99%
“…All studies regarding edentulism were crosssectional studies. Only two studies, showing either no significant association or a negative association between edentulism and OHQoL, met all quality criteria of the AXIS tool (Hoeksema et al 2018;Rebelo et al, 2016). One cohort study of poor quality showed that participants with permanent tooth loss were most likely to both worsen and improve OHQoL (Astrom, Ekback, Ordell, & Gulcan, 2018).…”
Section: Natural Dentitionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could also be affected by factors such as chronic disease and degeneration of movement function, which may further cause psychological and nutritional problems (Blanco‐Aguilera et al, ; Deshpande & Amrutiya, ). Poor oral health conditions, such as tooth loss, can impact more than just physical function, nutrition, and socialization and may also influence quality of life, which argues for the importance of good oral health and the urgency to identify relevant factors affecting oral health (Bidinotto et al, ; Hoeksema et al, ; Masood, Newton, Bakri, Khalid, & Masood, ). Oral health promotion among middle‐aged and older adults is an important part of the public health nurses' role (U.S. Department of Health & Human Services Oral Health Coordinating Committee, ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to natural teeth, the loss of the natural dentition is associated with a lower quality of life (Albaker, ; Hoeksema et al, ). Edentulous patients with implant‐supported restorations, however, have a higher quality of life than patients with complete dentures (Emami, Heydecke, Rompre, Grandmont, & Feine, ; Thomason, ).…”
Section: Introductionmentioning
confidence: 99%